The Goonies - Donner, Richard ([s.l.] Steven Spielberg, 1985)
The Goonies plunges a band of small heroes into a swashbuckling, surprise-around-every-corner quest beyond their wildest dreams. Following a mysterious treasure map into a spectacular underground realm of twisting passages, outrageous booby-traps and a long-lost pirate ship full of golden doubloons, the kids race to stay one step ahead by a family of bumbling bad guys... and a mild mannered monster with a face only a mother could love.
VCD
Story by Steven Spielberg, screenplay by Chris Columbus, music by Dave Grusin ; produced by Richard Donner and Harvey Bernhard ; directed by Richard Donner
Sean Astin, Josh Brolin, Jeff Cohen
Keywords: Feature films